The frequency and clinical course of retinopathy of prematurity in modern developmental care conditions as evidenced by the Moscow region perinatal center - L. A. Katargina; S. A. Trusova; O. A. Shevernaya; N. A. Osipova; A. Yu. Panova (Российский офтальмологический журнал, 2020)
Purpose: to determine the incidence and clinical course of retinopathy of prematurity (ROP) in modern developmental  care conditions as based by the data of a level III perinatal center.Material  and methods. A retrospective study of 920 premature infants of the ROP at-risk cohort managed by the Neonatology department of Moscow Regional Perinatal Center over the 2-year period of 2017–2018 was performed. Retinopathy  was graded and treated following the respective Federal clinical guidelines.Results. Of the 920 infants who met the screening criteria, ROP was detected in 193 (28.5 %) infants; 49 infants (7.2 %) required treatment.  Of all general somatic factors, the duration of artificial ventilation of lungs showed the strongest correlation with the frequency of development and severity of ROP.  In infants with birth weight > 1000 g, the incidence of severe forms of ROP correlated with the presence of necrotizing enterocolitis and intraventricular  hemorrhages, while in children with a lower body weight at birth no such correlation was detected. Bronchopulmonary dysplasia was not found to affect the development of ROP.  In groups of infants with birth weight of 1000–1499 g and 500–999 g, the frequency of transfusions of washed red blood cells with depleted leukocyte and thrombocyte levels was generally higher in children with ROP, both with spontaneous and induced regression, but showed no difference between the two subgroups.Conclusion. Severe somatic pathology does not always accompany the progression of ROP to the threshold stage. So, in order to optimize ROP screening, it is necessary to search for new more accurate criteria for ROP development and progression risk.